GOVERNANCE OF E-COMMERCE TECHNOLOGY DOWNSTREAMING IN EMPOWERING MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) IN TRADITIONAL CULINARY BUSINESSES - Zulfachry, Zulfachry; Jafar, Nurhidayah; Nursalsabila, Nursalsabila; Sasmika, Defi; Rachmat, Zul; Fadli, Zul (INSTITUT TEKNOLOGI DAN BISNIS PGRI DEWANTARA JOMBANG, 2026)
This study analyzes the implementation of technology downstream governance in e-commerce for empowering traditional culinary MSMEs in Soppeng Regency, South Sulawesi. Using a mixed-methods approach, the research involved 156 traditional culinary MSMEs distributed across 8 sub-districts as the population, with 30 MSMEs as representative samples. Data collection was conducted through structured surveys, in-depth interviews, and direct observations of three stakeholder categories: MSME actors, supporting institutions, and technology developers. The results show that 70% of MSMEs use WhatsApp Business as their primary platform with a satisfaction level of 4.2/5. E-commerce implementation in three pilot MSMEs resulted in significant improvements: market reach increased by 700%, monthly turnover rose by 35%, and customer numbers grew by 40% within 6 months. The main challenges identified include limited technical skills (priority index 1), digital payment systems (priority 2), and technology investment capital (priority 3). The research developed an integrated governance framework with five pillars: digital infrastructure, human capital development, financial ecosystem, technology integration, and governance monitoring. The developed model proved effective in enhancing the competitiveness of traditional culinary MSMEs and can be replicated in other regions with similar characteristics. The study contributes to the understanding of technology governance in MSME digitalization and provides practical recommendations for sustainable digital transformation in the traditional culinary sector.